Windows of peace: The effect of ceasefires on economic recovery - Alex Armand; Myriam Marending; Galina Vysotskaya (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
While much of the literature studies causes and consequences of war, the reverberations of peace have rarely been studied. By focusing on the universe of ceasefire agreements since 1993, we study the causal effect of peace on economic recovery using a regression discontinuity in time approach. We estimate these impacts by temporally and spatially matching information on ceasefires with granular data about violence and economic recovery, allowing us to observe their dynamics at highly disaggregated levels and in temporal proximity to their entry into force. Overall, ceasefires have a marginal effect on violence, with their effectiveness in curbing hostilities being greater in areas where conflict is active closer in time to the agreement. These effects are driven by reductions in state-based conflicts, while other types of hostilities or civilian involvement remain unaffected. Using high-frequency data on night-time luminosity, we show that ceasefires have a positive impact on economic recovery, corresponding to an increase of 5.5 per cent when the agreement enters into place. Despite the effect being temporary, we find that it is not driven by external interventions, such as internationally funded new development projects or peace missions.
Keywords: D74; F5; O1; O20; 330; peace; conflict; agreement; ceasefire; development; recovery